Facts about Vitamin D - Linda B. Bobroff; Isabel Valentin-Oquendo (EDIS)
Vitamin D is needed for normal absorption of calcium and phosphorus. It helps put these minerals into bones and teeth. This makes bones stronger and reduces risk for bone fractures. Vitamin D also helps keep the immune system functioning normally, so our bodies can resist some types of disease. This revised 2-page fact sheet was written by Linda B. Bobroff and Isabel Valentín-Oquendo, and published by the UF Department of Family, Youth and Community Sciences, February 2014.